How I as a Fundraiser Would Use Twenty Million Dollars for Anti-Trafficking Work - Gupta, Kiran (Anti-Trafficking Review, 2024)
Representations of human trafficking in film and media have widely missed the mark by misinforming the public and funders and harming those with lived experience. This has real implications for the anti-trafficking movement, including a lack of sufficient financial support for victim services and the failure to implement long-term systemic change. To change this, this article argues that we must invest in narrative change around human trafficking, under the leadership of those with lived experience. If done well, this could potentially bring additional funding for services by reaching the wider public, and even move the needle on trafficking prevention.